High frequency of de novo mutations in Li–Fraumeni syndrome. Issue 10 (25th June 2009) - Gonzalez, K D; Buzin, C H; Noltner, K A; Gu, D; Li, W; Malkin, D; Sommer, S S
Abstract : Background: Li–Fraumeni syndrome is an autosomal dominant cancer predisposition syndrome caused by germline mutations in the TP53 gene. The frequency of germline de novo TP53 mutations is largely unknown; few unequivocal de novo mutations have been reported. Methods and results: Of 341 patients with early onset cancer sent for clinical testing to a national reference laboratory, 75 patients had TP53 germline mutations. Five (7%) de novo mutations were identified, as well as an additional 10 TP53 germline mutations likely to be de novo by family history. The frequency of de novo TP53 mutations in this patient sample is at least 7% and may be as high as 20%. Conclusions: The possibility that de novo germline TP53 mutations are relatively common has implications for testing and the identification of potential Li–Fraumeni syndrome in patients with little or no family history of cancer.